miR-221-5p-Mediated Downregulation of JNK2 Aggravates Acute Lung Injury - Jing Yang (Frontiers Media S.A., 2021)
Sepsis and acute lung injury (ALI) are linked to mitochondrial dysfunction; however, the underlying mechanism remains elusive. We previously reported that c-Jun N-terminal protein kinase 2 (JNK2) promotes stress-induced mitophagy by targeting small mitochondrial alternative reading frame (smARF) for ubiquitin-mediated proteasomal degradation, thereby preventing mitochondrial dysfunction and restraining inflammasome activation. Here we report that loss of JNK2 exacerbates lung inflammation and injury during sepsis and ALI in mice. JNK2 is downregulated in mice with endotoxic shock or ALI, concomitantly correlated inversely with disease severity. Small RNA sequencing revealed that miR-221-5p, which contains seed sequence matching to JNK2 mRNA 3’ untranslated region (3’UTR), is upregulated in response to lipopolysaccharide, with dynamically inverse correlation with JNK2 mRNA levels. miR-221-5p targets the 3’UTR of JNK2 mRNA leading to its downregulation. Accordingly, miR-221-5p exacerbates lung inflammation and injury during sepsis in mice by targeting JNK2. Importantly, in patients with pneumonia in medical intensive care unit, JNK2 mRNA levels in alveolar macrophages flow sorted from non-bronchoscopic broncholaveolar lavage (BAL) fluid were inversely correlated strongly and significantly with the percentage of neutrophils, neutrophil and white blood cell counts in BAL fluid. Our data suggest that miR-221-5p targets JNK2 and thereby aggravates lung inflammation and injury during sepsis.